Implementation of REDD+ Mechanisms in Tanzania - Cordero Cordero, Paula (World Bank, Washington, DC, 2014)
This paper explains the major issues and lessons derived from the national forest management program and REDD+ initiatives in Tanzania. It finds that addressing the most important drivers of forest degradation and deforestation, in particular the country energy needs and landownership, is essential for success in reducing emissions regardless of the type of program implemented. It also finds that, through the national program, forest users have learned to maximize profit from the sustainable use of the forest; however, the program reports great variability in the success of forest conservation. REDD+ may complement the national program by adding funding and other resources to start projects at the local level while giving additional payments for the permanence of carbon stocks may help to improve the social outcomes of those villages practicing sustainable forest management. However, a careful characterization of the national projects is necessary to generalize how REDD+ can be effectively implemented so that additional economic and environmental benefits are generated over what the national program is already achieving. Addressing this issue is key for identifying the conditions under which REDD+ achieves environmental additionality in Tanzania.